y=-log(3)*(3x-6)

Simple and best practice solution for y=-log(3)*(3x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-log(3)*(3x-6) equation:


Simplifying
y = -1log(3)(3x + -6)

Reorder the terms:
y = -1glo * 3(-6 + 3x)

Reorder the terms for easier multiplication:
y = -1 * 3glo(-6 + 3x)

Multiply -1 * 3
y = -3glo(-6 + 3x)
y = (-6 * -3glo + 3x * -3glo)
y = (18glo + -9glox)

Solving
y = 18glo + -9glox

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 18glo + -9glox

See similar equations:

| v/3-4=1 | | 2.3+1.8a=5.1 | | 0x=-14 | | 2.1b+45.2=3.2-8.4b | | 8-t=10-7 | | z/11=11 | | 8-7=k/11 | | w+11=12 | | 12v+12v=1 | | a/3=6-1 | | -1y-2x=9 | | 100/45=14 | | 5m+24=29 | | 9+14=y | | 6x-280=180 | | 12x+14x+3y= | | -x-41=4(5x-5) | | 4(2x-3)-10=5x+5 | | X+6x-280=180 | | x/50=0.20 | | 2(x+6.2)+2.2=8.7x+7 | | -8.3=5(-1.4-b) | | 2x+y=264 | | 8(s-1)-6.1=2.9s+8 | | (2x-1)/3=1-x | | 14m+4n-5m+7n= | | (2x-1)/3=1_x | | z=4x^2+y^2-6x | | 2(x-3)=3(2x-10) | | -9(5f-4)=-31+3f | | x-45=-60 | | 25-3y=-8(7y-4) |

Equations solver categories